2013
DOI: 10.1002/ca.22240
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic isolated partial hiatal herniation of the pancreas: MDCT evaluation and anatomical explanation: Case report and review of literature

Abstract: Isolated herniation of the pancreas through a gastroesophageal hiatus is an extremely rare condition, and only one case has been reported in the world literature. We describe a MDCT diagnosis of isolated partial hiatal hernia containing the body of a normal pancreas in an asymptomatic patient, give an anatomical explanation and review the corresponding literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…They have been reported in congenital [11,15,18] and acquired hernias [3,4,6,10,12,14,16,19,20], but also as rare longterm complication after both transhiatal and transthoracic esophagectomy [8,9]. Even isolated (possibly congenital) herniation of just the pancreas [2] and transient pancreatic herniation have been reported [6,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They have been reported in congenital [11,15,18] and acquired hernias [3,4,6,10,12,14,16,19,20], but also as rare longterm complication after both transhiatal and transthoracic esophagectomy [8,9]. Even isolated (possibly congenital) herniation of just the pancreas [2] and transient pancreatic herniation have been reported [6,14].…”
Section: Discussionmentioning
confidence: 99%
“…When the colon and small intestine are herniated, stretching of transverse mesocolon may allow mobilization of the pancreas after lengthening of the posterior adhering fascia [2,6]. In a recent human cadaver study, researchers found retropancreatic fascia lining the posterior aspect of the body of the pancreas but were unable to locate the anterior renal fascia, possibly due to degeneration of the adrenal gland with ageing [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fusion fascia is termed the fascia of Treitz behind the head and the fascia of Toldt behind the body and tail of the pancreas. 2,3 The ablation of this fusion is possible and reversible as is the case during pancreaticoduodenectomies (Kocher maneuver).…”
Section: Transhiatal Herniation Of the Pancreas: An Extremely Rare Simentioning
confidence: 99%